2021
DOI: 10.3389/fgene.2021.727233
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization Analysis of Thalassemia and Hemoglobinopathy in Quanzhou, Southeast China: A Large-Scale Retrospective Study

Abstract: Background: There are limited reports available on investigations into the molecular spectrum of thalassemia and hemoglobinopathy in Fujian province, Southeast China. Here, we aim to reveal the spectrum of the thalassemia mutation and hemoglobinopathy in Quanzhou prefecture, Fujian province.Methods: We collected data from a total of 17,407 subjects with the thalassemia trait in Quanzhou prefecture. Gap-PCR, DNA reverse dot blot hybridization, and DNA sequencing were utilized for common and rare thalassemia gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(50 reference statements)
3
11
1
Order By: Relevance
“…The high-frequent genotypes of α-thalassemia in the Han were αα/-- SEA (25.55%), -α 3.7 /αα (22.17%), -α 4.2 /αα (21.59%), α WS α/αα (8.93%), -α 3.7 /-α 4.2 (4.17%), and α QS α/αα (3.96%), and those of Li were -α 4.2 /αα (17.24%), -α 3.7 /αα (17.16%), -α 3.7 /-α 4.2 (15.09%), α WS α/αα (9.69%), α WS α/-α 3.7 (8.06%), -α 3.7 /-α 3.7 (7.45%), αWSα/-α4.2 (7.13%), and -α 4.2 /-α 4.2 (7.11%). The αα/-- SEA was the highest genotype of α-thalassemia in the Han nationality, which was similar to the reports from other provinces in China ( He et al, 2018 ; Peng et al, 2021 ; Zhuang et al, 2021 ). However, αα/-- SEA only accounts for 1.87% of α-thalassemia in the Li nationality, far lower than other high-frequent genotypes, which was the biggest difference between the Li nationality and the Han nationality.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The high-frequent genotypes of α-thalassemia in the Han were αα/-- SEA (25.55%), -α 3.7 /αα (22.17%), -α 4.2 /αα (21.59%), α WS α/αα (8.93%), -α 3.7 /-α 4.2 (4.17%), and α QS α/αα (3.96%), and those of Li were -α 4.2 /αα (17.24%), -α 3.7 /αα (17.16%), -α 3.7 /-α 4.2 (15.09%), α WS α/αα (9.69%), α WS α/-α 3.7 (8.06%), -α 3.7 /-α 3.7 (7.45%), αWSα/-α4.2 (7.13%), and -α 4.2 /-α 4.2 (7.11%). The αα/-- SEA was the highest genotype of α-thalassemia in the Han nationality, which was similar to the reports from other provinces in China ( He et al, 2018 ; Peng et al, 2021 ; Zhuang et al, 2021 ). However, αα/-- SEA only accounts for 1.87% of α-thalassemia in the Li nationality, far lower than other high-frequent genotypes, which was the biggest difference between the Li nationality and the Han nationality.…”
Section: Discussionsupporting
confidence: 86%
“…The results showed that the five most common mutations of α-thalassemia were -α 3.7 , -α 4.2 , -- SEA , α WS α, and α QS α, which account for 99.15% of all α-thalassemia carriers. These results suggested that the molecular profile of α-thalassemia in Hainan was different from that which is previously depicted in southern China, such as Guangxi, Guangdong, and Fujian, where-- SEA and α CS α always had higher allele frequencies, and-- SEA usually has the highest allele frequency ( He et al, 2018 ; Peng et al, 2021 ; Zhuang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…According to different genetic backgrounds and migration, the mutational spectrum of β-thalassemia and SNP frequency in southern Thai differed in other parts of Thailand. This phenomenon has also been observed in various countries such as India ( 42-44 ), Malaysia, China ( 45 , 46 ), and other countries ( 47 ). Therefore, the predictive performance of the β-thalassemia mutations and SNPs would differ in each region in the same country.…”
Section: Discussionmentioning
confidence: 60%
“…Although this study recruited patients from several provinces of southern Thailand, a similar pattern of the most common β-thalassemia mutations was observed. The origin of patients may explain the difference in distribution; for example, codons 41/42 (-TTCT) are very common in individuals of Chinese origin ( 45 , 46 ), whereas IVS I-5 (G>C) is very common in the Malay ( 49 ) and Asian Indian ( 50 ) populations. Interestingly, the present study demonstrated comparable frequencies of codons 41/42; -TTCT (23.9%) and IVS I-5; G>C (23.4%) because of the higher sample size of Thai-Muslim patients.…”
Section: Discussionmentioning
confidence: 99%